Boundary value problems of mathematical physics Volume II - Stakgold, Ivar (New York Macmillan, 1968)
Contents: distributions and generalized solutions; potential theory; equations of evolution; variational and related methods.
Includes bibliographical references and indexes.
Keywords: Cơ bản